Efektivitas Strategi Pembelajaran Inkuiri pada Pembelajaran IPS di MI/SD - Pijay Pijay; Panji Maulana Yusup; Oman Farhurohman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to explore the effectiveness of inquiry learning strategies in Social Sciences (IPS) learning at the Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels. The method used in this research is a literature study, which collects and analyzes various references from articles, books and journals that discuss the application and results of using inquiry strategies in educational contexts. The results of the analysis show that inquiry learning strategies can increase students' active involvement, improve understanding of social studies concepts, and develop critical thinking and problem solving skills. However, the effectiveness of this strategy is greatly influenced by factors such as the teacher's skills in managing the class, students' readiness for independent learning, and facilities that support the implementation of learning. In addition, challenges that arise in its implementation include limited time available in the curriculum and a lack of resources that support optimal use of inquiry strategies. However, overall, this research concludes that inquiry learning strategies can improve the quality of social studies learning, and to achieve optimal results, it is necessary.